THE DEVELOPMENT OF THE UKRAINIAN AIRPORTS INFRASTRUCTURE ACCORDING WITH THE INTERNATIONAL EXPERIENCE - Павелко, Віталій (Управління змінами та інновації, 2023)
The article discusses the pre-war state of the Ukrainian airports infrastructure and determines the list of problems which interfere the development of aviation branch of Ukraine. The article considers, that airport as a single complex, consists of the list of manufacturing infrastructure objects, which are obliged to regular investments for its development, reconstruction or new construction. For its operation, airport should provide full maintains of flights according with the air companies’ standards, demands and rules of security. The problem with the runway destruction is the main trouble of the Ukrainian regional airports and one of the main state airports development initiatives direction. The another important infrastructure element of each airport is a terminal. So, one of the reasons of the Ukrainian airports infrastructure critical level is a permanent underfunding, which makes not only the production threatening, but also the national security. The article proves, that all Ukrainian airports are in need of modernization runways, terminals, buildings, special technics and equipment to meet the international certification requirements. Some airports are in need of renovation, but the most of the Ukrainian airports are in need of full reconstruction. So, because of the airport activity is capital intensive and needs big investments, the main way of the Ukrainian airports infrastructure development in accordance with the international experience is the state-private partnership.